Reaction kinetics of Powder River Basin coal gasification in carbon dioxide using a modified drop tube reactor. (15th January 2015) - Wang, Ying; Bell, David A.
Highlights: The rate of Powder River Basin coal gasification was measured in carbon dioxide. A novel design of a modified drop tube reactor with rapid response analyzing system was developed. The reaction rate and carbon conversion was determined at 833–975 °C and 1–12 atm. The kinetics results can be described by the random pore model. Surface characteristics measurements (surface area measurements, scanning electron microscope images) were presented. Abstract: Carbon dioxide gasification and coal pyrolysis rates were measured in a modified drop tube fixed bed reactor, accompanied with a rapid response, real-time gas analysis system. Rapid heating and fast pyrolysis of the coal sample are intended to approximate the injection of ambient temperature coal into a fluidized bed gasifier. Experiments were done from 833 °C to 975 °C and from 1 atm to 12 atm in a 4:1 mixture of CO2 and argon with coal particles ranging between 250 μm and 850 μm. Reaction rates and carbon conversions were calculated based on the CO signal from a quadrupole mass spectrometer. The random pore model closely fits the experimental results and fitting parameters are listed. Results from the effects of temperature and pressure, pyrolysis conditions, and characteristics of chars (surface area measurements, scanning electron microscope images) are presented.